Transcriptional and Epigenomic Regulation of Adipogenesis - Lee, Ji-Eun; Schmidt, Hannah; Lai, Binbin; Ge, Kai (Molecular and cellular biology, 2019)
Understanding adipogenesis, the process of adipocyte development, may provide new ways to treat obesity and related metabolic diseases. Adipogenesis is controlled by coordinated actions of lineage-determining transcription factors and epigenomic regulators. Peroxisome proliferator-activated receptor gamma (PPARγ) and C/EBPα are master "adipogenic" transcription factors. In recent years, a growing number of studies have reported the identification of novel transcriptional and epigenomic regulators of adipogenesis. However, many of these novel regulators have not been validated in adipocyte development in vivo and their working mechanisms are often far from clear. In this minireview, we discuss recent advances in transcriptional and epigenomic regulation of adipogenesis, with a focus on factors and mechanisms shared by both white adipogenesis and brown adipogenesis. Studies on the transcriptional regulation of adipogenesis highlight the importance of investigating adipocyte differentiation in vivo rather than drawing conclusions based on knockdown experiments in cell culture. Advances in understanding of epigenomic regulation of adipogenesis have revealed critical roles of histone methylation/demethylation, histone acetylation/deacetylation, chromatin remodeling, DNA methylation, and microRNAs in adipocyte differentiation. We also discuss future research directions that may help identify novel factors and mechanisms regulating adipogenesis.